2015
DOI: 10.1007/s11218-015-9296-8
|View full text |Cite
|
Sign up to set email alerts
|

Losing its expected communal value: how stereotype threat undermines women’s identity as research scientists

Abstract: The worry or concern over confirming negative gender group stereotypes, called stereotype threat, is one explanation for women's worldwide underrepresentation in undergraduate science classes and majors. But how does stereotype threat translate into fewer women motivated for science? In this quantitative study with a sample from the US, we use Expectancy Value Theory to examine whether and how stereotype threat concerns might influence women's science identification. To do this, we collected survey data from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 84 publications
(140 reference statements)
2
61
1
1
Order By: Relevance
“…Many of these studies also demonstrate how decreases in these psychological factors are the proximate mechanisms by which stereotype threat decreases performance or retention. Studies have found that stereotype threat reduces science identity for women in a range of disciplines including biology, chemistry, physics, and engineering and some of these studies also show that this reduction in science identity mediates some of the impact of stereotype threat on persistence [68,93,95,105]. Women under stereotype threat also seem to express reduced self-efficacy across diverse STEM disciplines and this impact on self-efficacy can also mediate some of the effect of stereotype threat on persistence [1,30,93,95,101].…”
Section: Stereotypes About Women's Ability In Stemmentioning
confidence: 94%
See 3 more Smart Citations
“…Many of these studies also demonstrate how decreases in these psychological factors are the proximate mechanisms by which stereotype threat decreases performance or retention. Studies have found that stereotype threat reduces science identity for women in a range of disciplines including biology, chemistry, physics, and engineering and some of these studies also show that this reduction in science identity mediates some of the impact of stereotype threat on persistence [68,93,95,105]. Women under stereotype threat also seem to express reduced self-efficacy across diverse STEM disciplines and this impact on self-efficacy can also mediate some of the effect of stereotype threat on persistence [1,30,93,95,101].…”
Section: Stereotypes About Women's Ability In Stemmentioning
confidence: 94%
“…Additionally, in a national sample of over 9000 college students, women's interest in helping others was negatively correlated with their persistence in STEM [120]. Finally, Smith et al [93] found that women in STEM who perceived that science could not address communal goals had weaker science identities and this lower science identity predicted their attrition from STEM. Based on these studies, one possible way to address the gender gap in persistence in STEM may be to increase the perception that science can support communal goals.…”
Section: Conflict Between Personal Goals and Stereotypes About The Prmentioning
confidence: 99%
See 2 more Smart Citations
“…When students perceive value in course topics, they develop greater interest, work harder, perform better, persist longer, take additional courses, and complete their degree programs (Harackiewicz et al, 2008; Hulleman, Durik, Schweigert, & Harackiewicz, 2008). Students who see the value of a field of study experience greater involvement, more positive task attitudes, and greater identification with the domain (Brown et al, 2015; Smith, Brown, Thoman, & Deemer, 2015). …”
Section: Interventions To Promote Motivationmentioning
confidence: 99%